Smooth endoplasmic reticulum aggregates in oocytes associated with increased risk of neonatal birth defects: A meta‐analysis - Rui Long; Meng Wang; Qiyu Yang; Yini Zhang; Limin Gao; Lei Jin; Lixia Zhu (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Previous studies have indicated the association between smooth endoplasmic reticulum aggregates (SERa+) and poorer medically assisted reproduction outcomes. However, the link between SERa+ and neonatal outcomes remains controversial and open for debate. A comprehensive meta‐analysis on the relation between SERa+ and the risk of birth defects is needed. Material and Methods The literature search was conducted using the following databases: PubMed, Embase, Cochrane Libraries, Web of Science, and Chinese databases including China National Knowledge Infrastructure (CNKI) and Wan Fang from inception until July 2023. Risk ratio (RR) and 95% confidence interval (CI) were calculated by a fixed‐effected model, while heterogeneity was assessed by forest plots and I2 statistic. Funnel plot was produced to assess publication bias. This meta‐analysis has been registered on PROSPERO (CRD42022313387). Results The search resulted in 122 studies, 14 of which met the inclusion criteria. The analysis of birth defects revealed a higher risk (RR = 2.17, 95%CI 1.24 to 3.81, p = 0.007) in children derived from SERa+ cycle compared to SERa‐ cycles (711 vs. 4633). Meanwhile, in a subgroup analysis, the risk of birth defects was significantly increased in the SERa+ oocytes group as compared with the sibling SERa‐ oocytes group (RR = 3.53, 95%CI 1.21 to 10.24, p = 0.02). Conclusions To conclude, our analysis indicated that SERa+ cycles/oocytes may have a potential risk of increased additional major birth defects comparing with SERa‐ cycles/oocytes. This conclusion may provide evidence‐based support for clinicians in IVF clinical guidance and embryologists in prudent embryo selection strategy.